1997
DOI: 10.1074/jbc.272.12.8040
|View full text |Cite
|
Sign up to set email alerts
|

Strains of Synechocystis sp. PCC 6803 with Altered PsaC

Abstract: A psaC deletion mutant of the unicellular cyanobacterium Synechocystis sp. PCC 6803 was utilized to incorporate site-specific amino acid substitutions in the cysteine residues that ligate the FA and FB iron-sulfur clusters in Photosystem I (PS I). Cysteines 14 and 51 of PsaC were changed to aspartic acid (C14DPsaC, C51DPsaC, C14D/C51DPsaC), serine (C14SPsaC, C51SPsaC), and alanine (C14APsaC, C51APsaC), and the properties of FA and FB were characterized by electron paramagnetic resonance spectroscopy and time-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…We can envision two mechanisms to explain these results. Illumination of PS I at cryogenic temperatures result in reduction of F A in 76% and F B in 24% of the complexes (40). This distribution is similar to that calculated assuming an equilibrium between F B and F A with redox midpoint potentials at Ϫ580 mV and Ϫ520 mV, respectively (41).…”
Section: Discussionsupporting
confidence: 63%
“…We can envision two mechanisms to explain these results. Illumination of PS I at cryogenic temperatures result in reduction of F A in 76% and F B in 24% of the complexes (40). This distribution is similar to that calculated assuming an equilibrium between F B and F A with redox midpoint potentials at Ϫ580 mV and Ϫ520 mV, respectively (41).…”
Section: Discussionsupporting
confidence: 63%
“… 23 , 31 , 40 , 41 Exchanges of the [4Fe–4S] cluster coordinating cysteines to aspartate have been shown before to be functionally tolerated in the PsaC subunit of photosystem I, as well as in the small subunit of a [NiFe]-hydrogenase. 32 , 33 By following the occupancies of the [4Fe–4S] and [2Fe] cluster of the catalytically relevant H-cluster, we have been able to gain new insights into the importance of each individual cysteine coordinating the [4Fe–4S] cluster.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that the majority of the clusters were turned into an EPR silent state by the selected amino acid exchanges, an effect already observed for a [4Fe–4S] cluster within the PsaC subunit of photosystem I (exchange of cysteine to aspartate). 33 Furthermore, in the native protein, the [4Fe–4S] cluster coordinating cysteine 366 is exposed to the surface of the maturation channel, providing the site of covalent attachment of the [2Fe] site. 42 It was shown that upon variation of this bridging position the covalent linkage of the [2Fe] cluster to the [4Fe–4S] cluster, as well as to the protein, is no longer feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvents such as acetonitrile or dimethyl sulfoxide also induce spin mixtures in the synthetic analog [Fe 4 S 4 (SR) 4 ] 3Ϫ (R ϭ alkyl or aryl) (80). Finally, the 2[4Fe-4S] 2ϩ/ϩ PsaC protein mutants, C14D and C51D, are also known to be easily converted from S ϭ 3/2 to S ϭ 1/2 at the modified cluster upon binding to the photosystem I core complex, a situation that is likely to affect solvent accessibility (81)(82)(83)(84)(85) ϩ as the dominant species and S ϭ 1/2 and 5/2 as minor components (86). In Thauera aromatica ferredoxin, which contains cysteine only-ligated 2[4Fe-4S] 2ϩ/ϩ clusters, a spin mixture of S ϭ 3/2 and 5/2 is observed for one cluster in the reduced state (87 cluster upon exposure to oxygen.…”
Section: Reduction Of the [4fe-4s] 2ϩ Cluster Of C42d Versus Native Fmentioning
confidence: 99%